Investigating the effective factors on e-marketing of rural products using fuzzy inference systems (ICT approach) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The use of information and communication technology (ICT) as one of the technological advances of the new age and its tools, namely e-government, e-commerce, e-learning, etc. can, along with proper management, accelerate the development of e-market sales of rural products. Providing public welfare in these areas will provide significant assistance. Accordingly, in the present article, using fuzzy logic to examine the factors affecting the market for electronic sales of rural products in terms of four criteria, the rate of rural use of electronic services ICT offices, computer literacy, the use of experts, and knowledgeable emarketing in offices Rural ICT, rural office facilities and e-marketing are covered in MATLAB software. The results of extracting the sales market model with fuzzy logic show that encouraging the villagers to use the electronic services of rural ICT offices, increasing the computer literacy of the villagers, and increasing the facilities of the offices will increase the electronicsales market of rural products.